2006
DOI: 10.7863/jum.2006.25.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentations of Midgut Volvulus With the Whirlpool Sign

Abstract: Midgut volvulus can also appear much beyond the neonatal age group with a variety of clinical presentations, making the clinical diagnosis in such patients very difficult, if not impossible. Identification of the clockwise whirlpool sign on sonography is an accurate way of diagnosing this condition, which can preclude the need for further investigations and can allow prompt surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…Additionally, among 3 patients with a counterclockwise whirlpool sign, none had intestinal volvulus during laparotomy, again emphasizing the importance of the direction of rotation. In another report, Taori and coworkers 20 showed that in 8 cases of volvulus, the whirlpool sign was shown in all of them, indicating sensitivity of 100%. All cases had a clockwise direction.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, among 3 patients with a counterclockwise whirlpool sign, none had intestinal volvulus during laparotomy, again emphasizing the importance of the direction of rotation. In another report, Taori and coworkers 20 showed that in 8 cases of volvulus, the whirlpool sign was shown in all of them, indicating sensitivity of 100%. All cases had a clockwise direction.…”
mentioning
confidence: 91%
“…This sign was described in infants by Pracros and coworkers, 19 who found it in 15 of 18 infants with small-bowel volvulus, indicating high sensitivity. Since then, several reports have shown its accuracy in diagnosing volvulus in infants, [20][21][22][23][24] thus establishing its diagnostic efficacy.…”
mentioning
confidence: 99%
“…[9] It is also reported that US is very useful in the evaluation of gastrointestinal obstruction and can suggest the diagnosis in atypical clinical presentation of midgut volvulus. [10][11][12] The CT scan does not usually represent the initial diagnostic tool in children with small-bowel obstruction, although it can be used in patients with a long-standing obstruction and marked bowel distension and may be helpful to confirm an SBI after ultrasonographic evidence. [1,12] In our case, US was unable to identify the characteristic signs of intussusception, showing only marked bowel distension and a mass in the mesogastrium.…”
Section: Discussionmentioning
confidence: 99%
“…Midgut volvulus can also appear beyond the neonatal period and with a variety of clinical presentations, making the clinical diagnosis in such patients very difficult. Ultrasonography can correctly suggest the diagnosis in such atypical clinical presentations of midgut volvulus [9] (Fig. 6).…”
Section: Midgut Volvulusmentioning
confidence: 97%